The Effect of Supplementation Urea and Sulfur in Mixed Cassava Waste Fermented and Soyabean Cake Waste on Digestibility of Protein and Blood Urea Male Sheep - Bata, M; Suwandyastuti, SNO; Hidayat, Nur (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 1999)
Eighteen local male sheep were divided into 3 groups I,II and III based on the body weight 18.55±1.27, 15.79±0.67 and 13.14±1.33 kg respectively. Two level urea (2 and 3%) and three levels Sulfur (0.02 and 0.3%) as treatment, so pattern factorial 2x3 with Randomized Block Design used this experiment. All of the treatment get a same basal feed namely land-grass and concentrate with dry matter ratio 70:30. The total intake of dry matter was 4 % of body weight. The concentrate consist of cassava waste fermented and soyabean cake waste with dry matter ratio 77.50 : 22.50. Supplementation of urea and sulfur shown not significant interaction, but supplementation urea had effect high significantly (P<0.01) on digestibility of protein and sulfur only had effect significant (P<0.05) on blood urea. These result had indication that enriched urea in the diet could increase protein digestibility and sulfur level 0.2% could prevent NH3 absorption from rumen. (Animal Production 1(2): 75-81 (1999) Key Words: cassava waste, soyabean cake waste, fermentation, digestibility, urea blood.